2015
DOI: 10.1177/0270467615616297
|View full text |Cite
|
Sign up to set email alerts
|

Public Perspectives on Risks and Benefits of Forensic DNA Databases

Abstract: There is scarce knowledge about the influence of the professional group, education, and age on public perspectives on the risks and benefits of forensic DNA databases. Based on data collected through an online questionnaire applied to 628 individuals in Portugal, this research fills that gap. More than three quarters of the respondents believed that the Portuguese forensic DNA database can help fight crime more efficiently and develop a swifter and more accurate justice, whereas only approximately half thought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Most quantitative studies were conducted in European countries—Spain [51, 52], Portugal [11, 55], Switzerland [56], Serbia [47], Italy [57]—and the remaining derived from the USA [43, 50] and New Zealand [53, 54]. The studies were published between 2001 [50] and 2018 [43].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most quantitative studies were conducted in European countries—Spain [51, 52], Portugal [11, 55], Switzerland [56], Serbia [47], Italy [57]—and the remaining derived from the USA [43, 50] and New Zealand [53, 54]. The studies were published between 2001 [50] and 2018 [43].…”
Section: Resultsmentioning
confidence: 99%
“…• More educated: less likely to agree that forensic DNA database can influence in developing swifter and more accurate justice [55]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with research by Wilson-Kovacs, Wyatt & Hauskeller [58], who compared different uses of genetic technologies and found that forensic DNA was the least problematic of genetic applications in the UK. Also, some scholars found wide support for a National Forensic DNA Database in England, Wales, Spain and Portugal [31,59,60].…”
Section: Discussionmentioning
confidence: 99%